2017
DOI: 10.20960/nh.1404
|View full text |Cite
|
Sign up to set email alerts
|

Use of nutritional supplements and ergogenic aids in professional tennis players

Abstract: López-Samanes Á, Moreno-Pérez V, Kovacs MS, Pallarés JG, Mora-Rodríguez R, Ortega JF. Use of nutritional supplements and ergogenic aids in professional tennis players. Nutr Hosp 2017;34:1463- ResumenIntroducción: los suplementos nutricionales/ayudas ergogénicas (NS&EA) son utilizados en los entrenamientos/partidos de tenis con el objetivo de mejorar el rendimiento. Sin embargo, la literatura científica se encuentras escasos documentos científicos sobre el uso de estas sustancias en tenistas profesionales. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
2
20
2
Order By: Relevance
“…Our first research finding was that all the international-level players consume NS, so that the consume prevalence is higher than the one observed in international-level players of tennis, in which it reaches 81% [ 15 ]. In addition, it has been found that consumption among international-level players is significantly higher than among national-level players ( p = 0.02) whose consumption rate is below 70%, which is confirmed by the results that were brought by a meta-analysis that concluded that elite athletes show a higher NS consumption rate [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first research finding was that all the international-level players consume NS, so that the consume prevalence is higher than the one observed in international-level players of tennis, in which it reaches 81% [ 15 ]. In addition, it has been found that consumption among international-level players is significantly higher than among national-level players ( p = 0.02) whose consumption rate is below 70%, which is confirmed by the results that were brought by a meta-analysis that concluded that elite athletes show a higher NS consumption rate [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for caffeine consumption in international-level squash players, it has been reported to be lower than in tennis players [ 15 ]. Caffeine acts as an important activator of the central nervous system, due to its effect as adenosine receptor antagonist, reducing effort perception during exercise and increasing the release of endorphins, and improving the neuromuscular function as well as that of the vigilance and alert state [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, creatine monohydrate supplementation has been used as a strategy to increase muscle mass and strength during training, but it has been also reported to improve power and anaerobic capacity [48][49][50]. Thus, the use of creatine in intermittent sports such as racquet sports is of high interest since about 75% of top 100 rank tennis players take it [17]. However, up to the present, there is no evidence for recommendation.…”
Section: Effects Of Creatine Monohydrate In Racquet Sportsmentioning
confidence: 99%
“…High performance in tennis is associated with higher values of strength and power output [5], agility [6], and serve velocity [7]. Other secondary determinant aspects have been proposed, such as environmental [8], nutrition [9], chronobiological aspects [10], and recovery strategies [11].…”
Section: Introductionmentioning
confidence: 99%